Melody in music therapy : a therapeutic narrative analysis - Aldridge, Gudrun, 1947- (J. Kingsley, 2008)
Melody is thought to be an 'essential core' of music. In the context of music therapy, looking at how patients develop their own melodies in improvisation can explain how they find their own voice, determine their position in relation to the world, and play an important role in how they relate to their therapist. Gudrun Aldridge and David Aldridge explore the concept of melody within its historical context and investigate current theories of melody. They make recommendations for choosing an appropriate method of analysing melodic improvisation, and utilise case studies to demonstrate these ana.